Recent Advances: The Imbalance of Cytokines in the Pathogenesis of Inflammatory Bowel Disease - Qingdong Guan; Jiguo Zhang (Mediators of Inflammation)
Cytokines play an important role in the immunopathogenesis of inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, where they drive and regulate multiple aspects of intestinal inflammation. The imbalance between proinflammatory and anti-inflammatory cytokines that occurs in IBD results in disease progression and tissue damage and limits the resolution of inflammation. Targeting cytokines have been novel strategies in the treatment of IBD. Recent studies show the beneficial effects of anticytokine treatments to IBD patients, and multiple novel cytokines are found to be involved in the pathogenesis of IBD. In this review, we will discuss the recent advances of novel biologics in clinics and clinical trials, and novel proinflammatory and anti-inflammatory cytokines found in IBD with focusing on IL-12 family and IL-1 family members as well as their relevance to the potential therapy of IBD.